2013
DOI: 10.1590/0004-282x20130141
|View full text |Cite
|
Sign up to set email alerts
|

Prosody and levodopa in Parkinsons disease

Abstract: Objective Research is scarce regarding the use of prosodic parameters in the expression of attitudes in Parkinson’s disease (PD). The purpose of this study was to evaluate the parameters used in prosodic expression of attitudes in individuals with idiopathic PD and the effect of levodopa on these parameters. Method We studied the use of levodopa in 10 individuals with idiopathic PD during the “off” and “on” periods, and 10 individuals without neurological abnormalities. Results PD patients showed lower fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…DA treatment does not have an effect on prosody, however it improves speech speed (Azevedo et al, 2013). DA treatment improved articulation, pitch variance, intensity and overall voice quality (Rusz et al 2013).…”
Section: Speech Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…DA treatment does not have an effect on prosody, however it improves speech speed (Azevedo et al, 2013). DA treatment improved articulation, pitch variance, intensity and overall voice quality (Rusz et al 2013).…”
Section: Speech Problemsmentioning
confidence: 99%
“…The findings from these two studies suggest that areas that are affected by PD also play a role in the cognitive component of speech production. In addition, Azevedo and colleagues suggested that bradykinesia may affect the prosody of the patients' speech (Azevedo, Reis, Souza, & Cardoso, 2013).…”
Section: Neural Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study 25 reported that the Parkinson disease does not make the patient use prosody to express his/her attitudes differently from the control group, however, when the attitudes were not taken into account, it was observed that levodopa was effective in the improvement of the parameter of duration. This finding reinforces the importance of the association of speech therapy to medication aiming to improve the communicative performance of parkinsonian patients.…”
Section: Discussionmentioning
confidence: 96%
“…Within this context, the paper published in this issue of Arquivos de Neuro-Psiquiatria by Azevedo et al 6 adds an important attempt to assess prosody using several acoustic and temporal speech measurements. In addition to extracting 12 selected parameters relating to the oral communication impact of PD, the authors aimed to investigate differences in expressing attitudes (certainty and doubt) and in modes of speech (declarative and interrogative), which have singular melodic patterns.…”
mentioning
confidence: 99%